Modernity through Letter Writing : Cherokee and Seneca Political Representations in Response to Removal, 1830-1857 - Haake, Claudia B. (Book collections on Project MUSE., 2020)
"Modernity through Letter Writing examines the discursive practices between both Native and non-Native writers during the Era of Removal. In this process of written diplomacy, protest, and petitioning, Native writers developed strategies for negotiating the policies of Indian Removal and advocating for their own indigenous nations"--